Distribuição estacional de forragem, valor nutritivo e rendimento de grãos de cereais de inverno de duplo propósito - Oliveira, Janete Taborda de (2009)
Crop-livestock systems compromise crop and animal production to improve performance using crop rotatios and pastures, by-produtos, hay and silage. Cultivars of winter crops with longer vegetative phase can be used as pasture of high nutritive value during crop season forage shortage in south brazilian conditions. Through adequate management practices may get high grain yield . Twenty four dual-purpose winter cereals were tested in two seeding date, April and May, harvested twice as green forage, which was estimated forage nutritive value and grain yield. BRS 277 yielded 2.224 kg DM/ha and BRS Guatambu whit 1.960 kg DM/ha were wheat cultivars detach to early forage production. In addition the new rye genotypes were detach on total biomass also in April seeding date. Although total biomass was not affect on May seeding date, there were grain yield reduction. PFT 307 triticale genotype seeded en aquil ord may 3.261 was detach on grain yield with kg/ha. On February and march seedings were not diference on forage yield among genotypes